2018
DOI: 10.3389/fchem.2018.00322
|View full text |Cite
|
Sign up to set email alerts
|

Bread Enriched With Legume Microgreens and Leaves—Ontogenetic and Baking-Driven Changes in the Profile of Secondary Plant Metabolites

Abstract: Flavonoids, carotenoids, and chlorophylls were characterized in microgreens and leaves of pea (Pisum sativum) and lupin (Lupinus angustifolius) as these metabolites change during ontogeny. All metabolites were higher in the leaves for both species. Acylated quercetin and kaempferol sophorotrioses were predominant in pea. Genistein and malonylated chrysoeriol were predominant in lupin. Further, the impact of breadmaking on these metabolites using pea and lupin material of two ontogenetic stages as an added ingr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
44
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(49 citation statements)
references
References 48 publications
4
44
1
Order By: Relevance
“…However, the phenolic compounds are possibly not easily extracted from the fiber matrix with only organic solvent. As described in the materials and method section, we have used methanol extraction following similar procedure as recommended and used in other publications and also by us on other brassica species [48][49][50]. However, the results from the present study indicate that additional phenolic compounds might be present in broccoli leaves not able to be extracted with methods generally adopted and commonly used for phenolics extraction in plants.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…However, the phenolic compounds are possibly not easily extracted from the fiber matrix with only organic solvent. As described in the materials and method section, we have used methanol extraction following similar procedure as recommended and used in other publications and also by us on other brassica species [48][49][50]. However, the results from the present study indicate that additional phenolic compounds might be present in broccoli leaves not able to be extracted with methods generally adopted and commonly used for phenolics extraction in plants.…”
Section: Discussionmentioning
confidence: 90%
“…All samples were analyzed in triplicates, and measurements of phenolic compounds were according to Lin et al [46], with some modifications as described below. Similar as in our previous study [47], a methanol extraction was applied as described below, following common practice for phenolic compounds [48][49][50].…”
Section: Analysis Of Phenolic Compoundsmentioning
confidence: 99%
“…Klopsch et al. () also found that mature leaves of pea and lupin had higher carotenoid concentrations than pea and lupin microgreens. Niroula et al.…”
Section: Microgreen Nutrient Contentmentioning
confidence: 93%
“…Klopsch et al. () added pea and lupin microgreens and mature leaves to bread dough to enhance the nutritional value of bread. In spite of the decline in carotenoids and chlorophylls, flavonoid levels were maintained with low losses during baking and significant pheophytin formation occurred.…”
Section: Microgreen Nutrient Contentmentioning
confidence: 99%
“…For the bread, a basic dough consisting of 41% wheat flour, 30% water, 8.5% rye flour, 18% sour dough, 1.5% salt, and 1.2% yeast was prepared. Sixty grams of fresh nasturtium leaves (roughly chopped, 2 × 2 cm) were then added to 500 g raw dough, so that these breads were fortified with 10.7% of nasturtium leaves . The plant material was incorporated carefully with a spiral mixer to avoid destruction of the plant material.…”
Section: Methodsmentioning
confidence: 99%